Geometria, modelagem e código de barras na construção de luminárias - Fernandes, Estela Aparecida (2013)
The presented work aims to allow students to infer about the different concepts by building Mathematicians luminaire. For this, occur following the development of a didactic, teaching methodology that consists in presenting the project to the students who undergo an initial production or initial assessment - production of texts, conversations, problems - from which different activities are performed, worked in modules on the topics. It is then rated the performance obtained through the production end. This methodology was applied to two classes of 2nd year of high school in a public school. The first step began with a presentation of the sequence followed by initial production, which allowed students to exhibit their knowledge of mathematics involved in the production end (luminaire). The proposal focuses on various topics from basic mathematics possible, through different methodologies, the resumption of constant content addressed thus enabling advances in the teachinglearning process. The topics taken up are observed in the plane geometry, which underlies the study of Space Geometry. The practice of mathematical modeling is used to rescue the concept of function with real meaning to students. The news was on account of the discovery of mathematics Barcode. And finally, the closing of the work took place with the presentation of the final production performed by students.